PENGARUH ECO ENZYME TERHADAP KANDUNGAN LOGAM BERAT LAHAN BEKAS TAMBANG BATUBARA - Zainudin Zainudin; Roro Kesumaningwati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Heavy metals are metallic elements with high molecular weight. Heavy metals are classified as essential and non-essential. Essential heavy metals are needed in small amounts, such as Fe, Mn, Cu, and Zn, while non-essential heavy metals are heavy metals that are not needed by living organisms such as Cd, Pb, Ag, Hg, and Cr. Heavy metal management aims to reduce the negative impact of soil contamination due to heavy metals. One of the heavy metals management is using organic materials. Eco enzymes are the result of fermentation of organic materials that are rich in microorganisms. Microorganisms are very important to help the decomposition process, transport nutrients, and degrade soil pollutants including heavy metals. This research aims to determine the effect of Eco Enzyme metal on the heavy content in the ex-coal mining soil. The study showed that the administration of eco-enzyme solutions with concentrations of 0%, 5%, 10%, 15%, and 20% gave the results of the analysis of heavy metals As, Pb, Hg, and Cd which were not much different, but the heavy metal content was in the normal range so that no harm to the soil.